2006
DOI: 10.1007/bf02898021
|View full text |Cite
|
Sign up to set email alerts
|

Nongenetic factors associated with human handedness and footedness in Japanese twin children

Abstract: It was concluded that factors that affect handedness or footedness in general, such as sex, birth year, age, parity, neonatal asphyxia, gestational age, birth complications, and family history, seem to have stronger effects on handedness and footedness than being a twin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
(42 reference statements)
2
19
0
Order By: Relevance
“…Although not impossible, it is very improbable that postnatal effects fully explain our results. One previous twin study found a lower prevalence of left footedness in females from opposite-sex pairs compared to females from same-sex pairs (Ooki, 2006). Relating to laterality, another twin study found that OSF twins had a right ear advantage on a dichotic listening task more often than SSF twins (Cohen-Bendahan et al, 2004).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Although not impossible, it is very improbable that postnatal effects fully explain our results. One previous twin study found a lower prevalence of left footedness in females from opposite-sex pairs compared to females from same-sex pairs (Ooki, 2006). Relating to laterality, another twin study found that OSF twins had a right ear advantage on a dichotic listening task more often than SSF twins (Cohen-Bendahan et al, 2004).…”
Section: Discussionmentioning
confidence: 86%
“…A second twin study reported no significant difference in left-handedness between females from opposite-sex and same-sex pairs in two separate samples (Ooki, 2006). In the first sample (N=1131, age 11–12) the prevalence of the left-handedness in opposite-sex females was 5.6% and 11.6% for same-sex female twins.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…When present study was performed, this school did not have an ethical committee for the twin study, which is now under construction, including the author as one of the advisers. Zygosity diagnosis using DNA sample was permitted through the ethical committee of the Graduate School of Medicine, University of Tokyo [51]. All the mothers in the maternal association group cooperated voluntarily in this research, mainly through the presidents of their associations [51].…”
Section: Ethical Issuesmentioning
confidence: 99%